Art therapy for PTSD and TBI: A senior active duty military service member's therapeutic journey. (July 2016) - Walker, Melissa S.; Kaimal, Girija; Koffman, Robert; DeGraba, Thomas J.
Graphical abstract: Highlights: Case study of long term art therapy with a senior military service member with PTSD and TBI. Senior military service member's injuries are under-reported and often under-addressed. Art therapy in the context of an integrative model of medical care is presented. Abstract: Art therapy is increasingly being accepted as a form of complementary and integrative care for military veterans affected by trauma and injuries in the line of duty. Less is known, however, about the applications of art therapy for co-morbid traumatic brain injury (TBI) and post-traumatic stress disorder (PTSD). In addition, most studies to date have focused on art therapy with veterans (former military service members) rather than with active duty service members; furthermore, there are no studies that have examined the unique context of PTSD in senior military personnel. This case study presents the therapeutic process through art therapy in the case of a senior active duty military service member (with chronic PTSD and TBI), in the context of an integrated model of care that included medical and complementary therapies.